2011
DOI: 10.1111/j.1468-2273.2011.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Ways to Increase Student Motivation: Internationalisation and Value Innovation

Abstract: Understanding what constitutes the perceived value of foreign education to international business students is critical for business schools in order to achieve their recruitment targets. One established method relies on a financial interpretation of the costs and benefits of business education. By contrast, this study advocates a holistic approach by employing the concept of "internal" and "external" career success as its theoretical underpinning. A survey of undergraduate Chinese students in two British busin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Support was a consistent consideration of research examining strategies that build expectancies and confidence to innovate (e.g., Kuznetsov & Kuznetsova, 2011 ). Common supports identified included creating a conducive innovation climate or culture (Dee et al, 2002 ; Hopkins, 2016 ; Kung & Chao, 2019 ; Montani et al, 2014 ; Susha et al, 2015 ), having reliable infrastructure (Susha et al, 2015 ), availability of mentoring (Apergis & Pekka-Economou, 2010 ), and inviting folks to engage with groups pursuing innovation (Apergis & Pekka-Economou, 2010 ; Curado et al, 2018 ; Messmann & Mulder, 2014 ; Radicic, Pugh, Hollanders, Wintjes, & Fairburn, 2016 ; Susha et al, 2015 ).…”
Section: Results For Expectancies In the Literature: Can I Do This?mentioning
confidence: 99%
See 1 more Smart Citation
“…Support was a consistent consideration of research examining strategies that build expectancies and confidence to innovate (e.g., Kuznetsov & Kuznetsova, 2011 ). Common supports identified included creating a conducive innovation climate or culture (Dee et al, 2002 ; Hopkins, 2016 ; Kung & Chao, 2019 ; Montani et al, 2014 ; Susha et al, 2015 ), having reliable infrastructure (Susha et al, 2015 ), availability of mentoring (Apergis & Pekka-Economou, 2010 ), and inviting folks to engage with groups pursuing innovation (Apergis & Pekka-Economou, 2010 ; Curado et al, 2018 ; Messmann & Mulder, 2014 ; Radicic, Pugh, Hollanders, Wintjes, & Fairburn, 2016 ; Susha et al, 2015 ).…”
Section: Results For Expectancies In the Literature: Can I Do This?mentioning
confidence: 99%
“…Effective collaboration was found to increase expectancies for innovation though necessitating the communication and subsequent discussion of ideas (Bastian et al, 2018 ; Curado et al, 2018 ; Fernandez & Pitts, 2011 ; Hartmann, 2006 ; Jiang & Thagard, 2014 ; Monge et al, 1992 ; Pihlajamaa, 2017 ). Collaboration was also found to involve diverse stakeholders (Aarikka-Stenroos et al, 2017 ; Costa et al, 2015 ; Kuznetsov & Kuznetsova, 2011 ; Sergeeva & Zanello, 2018 ; Wu et al, 2008 ), facilitate empowerment (Bolderdijk et al, 2018 ; Fernandez & Pitts, 2011 ), promote knowledge exchange (Aalbers et al, 2013 ; Antikainen & Vaataja, 2010 ; Bastian et al, 2018 ; Curado et al, 2018 ; Muninger et al, 2019 ; Naidoo & Sutherland, 2016 ), facilitate co-designing (Hartmann, 2006 ; Sorice & Donlan, 2015 ), inspire friendly competition between teams (Lam et al, 2010 ; Naidoo & Sutherland, 2016 ; Öberg & Shih, 2014 ), as well as help team and coalition building which ensure that a person does not have to go it alone (Costa et al, 2015 ; Dee et al, 2002 ; Kirsten & Du Preez, 2010 ; Mc Fadden & Gorman, 2016 ; Öberg & Shih, 2014 ). These outcomes of collaboration, such as networking (Mc Fadden & Gorman, 2016 ), all induced increases in confidence to innovate, especially in female entrepreneurial networks (Apergis & Pekka-Economou, 2010 ).…”
Section: Results For Expectancies In the Literature: Can I Do This?mentioning
confidence: 99%
“…It is widely agreed that well‐functioning academic staff groups and interpersonal collaboration is positively associated with student achievement and more productive higher education in general (Johnson, ; Brett et al ., ; Kuznetsov and Kuznetsova, ; Kelly and Moogan, ). It is assumed that effective academic staff groups will develop more relevant improvement plans and that the academics would have both the individual power and the loyal support to implement those plans both school‐wide and in their classrooms (Wheelan and Tilin, ).…”
Section: Conceptualisation and Theorymentioning
confidence: 99%
“…Accordingly, the increasing diversification of higher education staff could put new pressure on efforts to improve academic staff group functioning (Keller, ; Young and Brooks, ). This development is driven by demographic changes (Eddy and Gaston‐Gayles, ), by the emergence of an international academic labour market (Van De Bunt‐Kokhus, ; Gappa et al ., ; Mamiseishvili and Rosser, ) and by an increasing numbers of international students (Kuznetsov and Kuznetsova, ; Kelly and Moogan, ). However, although academic staff diversity may lead to problems, these may well be possible to overcome.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted at two Swedish universities concluded that even though motivation should be intrinsic, dedicated educators using a choice of teaching, learning and assessment methods, enhanced enthusiasm and learning. [6] This conclusion was further supported by [7] whose position was that "academic staff can enhance the effectiveness of learning interventions by using methodologies that go beyond traditional subject-related knowledge transfer." Extrinsic motivation in tertiary education works best when educators promote best practices like incorporating a variety of teaching methods and further, displaying verbal and non-verbal behaviours that create a positive impression and stimulate learners' interest.…”
Section: Introductionmentioning
confidence: 95%